Stress characterisation using lamb waves on nickel alloys - Ng, Jack Zhu Juan (Nanyang Technological University, 2020)
This study investigates the optimum operating frequency for guided waves in characterising stress in Al6061 and IN718. This was performed using a setup that could generate a guided wave of different frequencies within specimens of both materials, while applying varying levels of stress at the same time. From the received waveforms, a change in phase velocity against stress relationship was derived. Simulation models from other studies were also utilised to validate the accuracy of the experimental results. This study finds that for both materials analysed, lower frequencies are preferred for stress characterisation using guided waves, as lower frequencies suffer less from noise effects, with minimal trade-off in the ∆c_p against stress slope.